2011
DOI: 10.1200/jco.2010.33.8053
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Multicenter Trial of the Effects of Melanoma-Associated Helper Peptides and Cyclophosphamide on the Immunogenicity of a Multipeptide Melanoma Vaccine

Abstract: Purpose This multicenter randomized trial was designed to test whether melanoma-associated helper peptides augment CD8+ T-cell responses to a melanoma vaccine and whether cyclophosphamide (CY) pretreatment augments CD4+ or CD8+ T-cell responses to that vaccine. Patients and Methods In all, 167 eligible patients with resected stage IIB to IV melanoma were randomly assigned to four vaccination study arms. Patients were vaccinated with 12 class I major histocompatibility complex–restricted melanoma peptides (12MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
118
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(127 citation statements)
references
References 38 publications
7
118
2
Order By: Relevance
“…However, our findings are in contrast to previously published trials on peptide vaccination in patients with melanoma (37)(38)(39). In a recent randomized multicentre trial, Slingluff and colleagues report on 167 patients with stage IIB to IV melanoma vaccinated with either MHC-I-or MHC-I/II-restricted peptides, with or without cyclophosphamide pretreatment (37).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, our findings are in contrast to previously published trials on peptide vaccination in patients with melanoma (37)(38)(39). In a recent randomized multicentre trial, Slingluff and colleagues report on 167 patients with stage IIB to IV melanoma vaccinated with either MHC-I-or MHC-I/II-restricted peptides, with or without cyclophosphamide pretreatment (37).…”
Section: Discussioncontrasting
confidence: 56%
“…In a recent randomized multicentre trial, Slingluff and colleagues report on 167 patients with stage IIB to IV melanoma vaccinated with either MHC-I-or MHC-I/II-restricted peptides, with or without cyclophosphamide pretreatment (37). In this trial, the inclusion of melanoma-associated helper peptides paradoxically decreased CD8 þ T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study is the first to show a promising result indicating that therapeutic cancer vaccination with multiple peptides can potentially improve the prognosis of patients with advanced HNSCC refractory to standard therapy. Several phase II and III clinical trials have recently demonstrated promising and therapeutic results of cancer vaccination (19,(24)(25)(26)(27)(28)(29)(30)(31)(32). However, most of these studies were performed using single antigen-based vaccination with several modifications, and the clinical benefits appeared to be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the HAGE antigen is immunogenic and is highly associated with TILs, one should consider targeting HAGE along with other CSAs using immunotherapeutic interventions in conjunction with chemotherapy for TNBC. Although in the past, cancer vaccines have had a poor clinical track record due to poor clinical results (34), in recent trials using immunotherapy, clinical outcomes have shown improved progression-free survival, or overall survival (35)(36)(37)(38). In fact, it is proposed that chemotherapies could be used to condition the immune system and tumor, and create an environment in which cancer vaccines have a better chance of success (34,39).…”
Section: Discussionmentioning
confidence: 99%